The linguistic challenge in the Holy Quran Textual and Analytical Study - Ahmad, Zeravan Q.; Aoula, Ameer R. (Humanities Journal of University of Zakho, 2018)
This research aims to reveal the greatness of the Holy Quran, its superiority, and its miraculous statement, and that it is an argument for its imam. , And the challenge was gradually gradual depending on the situation they were on, because the Holy Quran is all few and much alike in miracles, and shows the need to challenge because it is evidence of the sincerity of the Prophet (peace be upon him) who came by the miracle, and challenge the Koran installed for his followers Peace be upon him), and strengthen his heart, because in every fit of The challenges of this challenge are a new miracle, as they are challenged every time to come up with a kind of bout of download.